Inflacja jako konsekwencja struktur społeczno-gospodarczych kapitalizmu - Barczyk, Ryszard; Kowalczyk, Zygmunt (Wydział Prawa i Administracji UAM, 1987)
Inflation is one of main problems appearing in contemporary highly developed capitalist economies. Due to low efficiency of implemented anti-inflation policies, the research into the causes, effects and means of fighting inflation is still being carried out. Yet Western studies in that field possess the character of fragmentary explanations and do not grasp the very essence of the process of the rise in prices. The article is an attempt to look anew, by means of the structural method, at the origin of inflation. The inflation processes in contemporary highly developed capitalist economies are the product of long-term, internal mechanisms functioning in capitalist structure. Socio-economic conditions of economic activity within that structure form the basis for certain disproportions, the sign of which is, inter alia, the inflation. (The structural changes indicated in the article confirm that the rise in prices coincides to a high degree with the transformations in the sector and branch structures of capitalist economies and with the differences in the dynamics of growth of labour efficiency and wages related to those transformations. Inflation processes are also correlated with interventionist policies of contemporary capitalist states.
Inflation as a consequence of socio-economic structures of capitalism